Using Logistic Regression to Predict Onset and Recovery With Tau Equivalency - Sorjonen, Kimmo; Lundberg, Michael; Melin, Bo (Frontiers in Psychology, 2018)
Many studies analyze the effect of a predictor X on the onset or recovery of an outcome Y, for example some kind of disorder. The findings from this simulation study indicate that such effects can be found even if there are no changes in individuals’ true scores on the outcome, i.e. with tau equivalency, given some degree of positive test-retest correlation of the outcome and a correlation between the predictor and the outcome at baseline. Researchers predicting onset/recovery should be aware of this fact and in order not to draw hasty conclusions to control for what can be expected from these correlations alone.